Fault detection of wind turbine gearbox using thermal network modelling and SCADA data. Issue 2 (September 2020) - Corley, B.; Carroll, J.; Mcdonald, A.
Abstract: This work uses a detailed understanding of the physics inside a wind turbine gearbox and SCADA temperature data as an alternative to data-driven techniques for fault detection. Thermal modelling based on the principles of heat transfer theory is used with the aim of understanding the thermal behaviour of a 'healthy' gearbox and use it to detect abnormal gearbox operating conditions. Data for turbines, 'healthy' and one month to fail, are analysed for two different failure modes to see if a fault can be detected in advance with the aim to improve physical understanding of wind turbine gearbox operation and condition monitoring techniques.